To die in Tuscany - Wagner, David P. (Wagner, David P. Rick Montoya Italian mysteries., 2021)
"Translator Rick Montoya is looking forward to a quiet weekend away in beautiful Urbino with his girlfriend, Betta, an art fraud investigator for the Italian Culture Ministry. While Betta does have official business-namely, collecting a priceless Piero drawing from a wealthy Spanish collector-she asks Rick to join her "in case she needs an interpreter," but with other, less-official intentions in mind. When the Spaniard is found murdered and the drawing stolen, Betta must shift back into art cop mode, and Rick's official services are required after all. Will this lovers' getaway literally be to die for?"--